2014
DOI: 10.3945/jn.113.188144
|View full text |Cite|
|
Sign up to set email alerts
|

Supplementation with Calcium and Short-Chain Fructo-Oligosaccharides Affects Markers of Bone Turnover but Not Bone Mineral Density in Postmenopausal Women

Abstract: This 24-mo randomized, double-blind, controlled trial aimed to examine whether supplementation with a natural marine-derived multi-mineral supplement rich in calcium (Ca) taken alone and in conjunction with short-chain fructo-oligosaccharide (scFOSs) has a beneficial effect on bone mineral density (BMD) and bone turnover markers (BTMs) in postmenopausal women. A total of 300 non-osteoporotic postmenopausal women were randomly assigned to daily supplements of 800 mg of Ca, 800 mg of Ca with 3.6 g of scFOS (CaFO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 41 publications
4
55
1
Order By: Relevance
“…Similarly, 4-weeks of FOS or DFAIII decreased resorption markers in gastrectomized rats (25). Consistent with the latter rodent studies, a randomized intervention study in post-menopausal women (average age 61) demonstrated that 24 months of short-chained FOS treatment reduced serum and urine bone turnover markers (42). …”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Similarly, 4-weeks of FOS or DFAIII decreased resorption markers in gastrectomized rats (25). Consistent with the latter rodent studies, a randomized intervention study in post-menopausal women (average age 61) demonstrated that 24 months of short-chained FOS treatment reduced serum and urine bone turnover markers (42). …”
Section: Introductionmentioning
confidence: 60%
“…As expected, short studies do not show changes in bone density, but a one year FOS treatment study was long enough to detect an increase in whole body bone mineral density in adolescent girls (30). Similarly, one year of FOS treatment reduced bone loss in post-menopausal women (42). …”
Section: Introductionmentioning
confidence: 99%
“…The only cross-sectional observational study (21) , to our knowledge, reported that dietary fiber was positively related to forearm BMD in children but not in adolescents. However, results from clinical trials in postmenopausal women are inconsistent: Although a positive association has been shown between fiber intake and calcium absorption (2225) , this does not translate to change in BMD (26,27) . Different directions of bone turnover markers were also reported (24,25,27) .…”
Section: Introductionmentioning
confidence: 99%
“…The prebiotic is fermented in the gut, causing a drop in the pH of the lumen to such an extent that previously insoluble calcium phosphate will dissolve. This plays a beneficial role in bone mineral density 50 . The fermentation of FOS releases short-chain fatty acids and lactic acid, which cause the drop in pH.…”
Section: Health-focused Researchmentioning
confidence: 99%